Service user experiences of a physical health group for people experiencing psychosis, designed following service user consultation - Rebecca Martland; Suzanne Jolley; Helen Harding (Psychiatry Research Communications, 2023)
Background: Psychosis is associated with physical health comorbidities. Exercise and a healthy diet can improve cardiometabolic risk and mental wellbeing. This study explores the feasibility, acceptability, and experiences of a physical health group for clients experiencing psychosis. Methods: The group was developed and refined following consultation with service-users and culturally appropriate peer support workers. It included eight weekly sessions. The aims of the group were to provide psychoeducation on healthy living and to build motivation to engage in healthy living. Attendance, completion, and satisfaction were recorded to determine feasibility and acceptability of local service delivery. Clients took part in follow-up qualitative interviews to understand experiences of attending the group. Interviews were analysed using thematic analysis. Results: Twenty-five clients were referred to the group. Overall, 10 clients enrolled in the group. Clients who enrolled in the group attended a median of 4.5 sessions. The mean satisfaction score for all sessions combined was 9.15/10 [SD 1.18]. Seven individual interviews were conducted. Two themes emerged. 1) Positive views towards the group, with clients feeling more aware of the benefits of healthy living, and clients finding the group setting motivating. 2) Considerations when planning healthy living support, which reflected subthemes in difficulties maintaining healthy living and concerns that the group should not be about weight loss. Limitations: Investigations were limited to one mental health provider. Conclusions: It was feasible and acceptable to implement a healthy living group for clients with psychosis in a community mental health team, and this intervention was met with positivity.